Penataan dan Verifikasi Data Sektoral EBT dan Minerba di Sumatera Selatan - Muhammad Fattan Attaur Rahman; Gusmelia Testiana (INDO PUBLISHING, 2026)
Accurate and standardized sectoral data management is a crucial requirement for local governments to support evidence-based policies as mandated by the One Data Indonesia policy. The South Sumatra Provincial Energy and Mineral Resources (ESDM) Office serves as a strategic data provider in the fields of new, renewable energy (EBT) and minerals and coal, but faces technical challenges in the form of non-uniform number formats, unit variations, digit limitations in the system, and data gaps in the raw dataset. This article is compiled from the results of the One Data Internship activities in the EBT and Coal Mineral Sectors for the period October–December 2025 with the aim of documenting the process of structuring, normalizing, and verifying three main datasets: EBT Mix Data, EBT Utilization Potential Data, and Coal Mineral Production Data. The methods used include field observation, analysis of data format suitability, technical implementation through template creation and input trials, and periodic evaluation of target achievement. The results of the activity show that all three datasets have been successfully updated until 2025 with a consistent format, standardized units to MW, and adjusted system capacity to be able to accept production figures without rounding. This achievement increases the credibility, interoperability, and readiness of data to be published transparently on the South Sumatra One Data Dashboard, while also contributing to the development of students' technical and professional competencies in government data management.